The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages QUESTIONS AND ANSWERS Q.— What relation is there between fatigue in industry and noise? A.— I would not like to answer with real certainty, but I would say the effect of noise on workers fatigue is not so great as is popularly imagined. If you are sensitive to noise then the matter is different. Q.— What effect does discontent over trivial matters have upon the health of workers? A.— Undoubtedly these so-called trivial things can have an important effect upon the health of the workers. For example, I know of two girls who arrived at work two minutes late and found the door shut against them. They had to go back home and their rage and annoyance made them ill. Trivial injustices and stupidities of this kind have a very serious effect upon health. Q.— As a miner I would like to know if sun-ray treatment has any good effect upon health? A.— That is another question whose answer I am not sure about. Under a sun-ray lamp I feel better but I am not sure if I am really better. I think you are a little better. I asked a trade union branch secretary what he thought about it once, and he replied, "fancy." I think sun-ray treatment is helpful, but as there is a shortage of equipment I would say, if I were a miner, that good grub should come first, then shorter hours of work, good ventilation, lighting, etc. is what I would go for. Q.— Is it normal procedure for a Factory Inspector, after receiving a complaint of bad sanitation, to report the matter to the management before making the investigation and following the investigation to send a written report to the management without any consultation with the workers? A.— That does not sound the usual procedure. Here is an experience which might help. I know of a big factory in Kent where the shop stewards asked the Factory Inspector to have a look round. There 12 15X/2/103/295